The Medicines Advice Service Evaluation (MASE): a randomised controlled trial of a pharmacist-led telephone based intervention designed to improve medication adherence. Issue 10 (11th January 2016) - Lyons, Imogen; Barber, Nicholas; Raynor, David K; Wei, Li
Abstract : Aim: To test the effectiveness of a tailored, pharmacist-led centralised advice service to improve adherence to patients on established medications. Methods: A parallel group randomised controlled trial was conducted. Patients prescribed at least one oral medication for type 2 diabetes and/or lipid regulation were eligible to participate. 677 patients of a mail-order pharmacy were recruited and randomised (340 intervention, 337 control). The intervention comprised two tailored telephone consultations with a pharmacist, 4–6 weeks apart, plus a written summary of the discussion and a medicines reminder chart. The primary outcome was self-reported adherence to medication at 6-month follow-up, collected via a postal questionnaire, analysed using generalised estimating equations. Secondary outcomes included prescription refill adherence, lipid and glycaemic control and patient satisfaction. Results: In intention-to-treat analysis 36/340 (10.6%) of the intervention group were non-adherent (<90% of medication taken in the past 7 days) at 6 months compared with 66/337 (19.6%) in the control group, yielding an unadjusted OR of 1.54 (95% CI 1.11 to 2.15, p=0.01). Analyses of dispensing data also showed that the odds of being classified as adherent (≥90%) were 60% greater for the intervention group compared with the control group (OR 1.60, 95% CI 1.14 to 2.24, p<0.01). In a subsample of patients who provided blood samples, glycaemic and lipid control did not differ significantly between groups (p=0.06 and p=0.24, respectively) but positive trends were observed. Ninety-two per cent of intervention group patients reported that they were satisfied with the service overall. Conclusions: A telephone intervention, led by a pharmacist and tailored to the individuals' needs, can significantly improve medication adherence in patients with long-term conditions, using a mail-order pharmacy. Further work is needed to confirm a trend towards improved clinical outcome. Trial registration number: NCT01864239.